A FINITE ELEMENT METHOD FOR DIELECTRIC ELASTOMER TRANSDUCERS - Qu, Shaoxing; Suo, Zhigang (Acta mechanica solida Sinica, 2012)
We present a finite element method for dielectric elastomer (DE) transducers based on the nonlinear field theory of DE. The method is implemented in the commercial finite element software ABAQUS, which provides a large library functions to describe finite elasticity. This method can be used to solve electromechanical coupling problems of DE transducers with complex configurations and under inhomogeneous deformation.